Plant Proteases: From Key Enzymes in Germination to Allies for Fighting Human Gluten-Related Disorders - Martinez, Manuel; Gómez-Cabellos, Sara; Giménez, María José; Barro, Francisco; Diaz, Isabel; Diaz-Mendoza, Mercedes (Frontiers in Plant Science, 2019)
Plant proteases play a crucial role in many different biological processes along the plant life cycle. One of the most determinant stages in which proteases are key protagonists is the plant germination through the hydrolysis and mobilization of other proteins accumulated in seeds and cereal grains. The most represented proteases in charge of this are the cysteine proteases group, including the C1A family known as papain-like and the C13 family also called legumains. In cereal species such as wheat, oat or rye, gluten is a very complex mixture of grain storage proteins, which may affect the health of sensitive consumers like celiac patients. Since gluten proteins are suitable targets for plant proteases, the knowledge of the proteases involved in storage protein mobilization could be employed to manipulate the amount of gluten in the grain. Some proteases have been previously found to exhibit promising properties for their application in the degradation of known toxic peptides from gluten. To explore the variability in gluten-degrading capacities, we have now analyzed the degradation of gluten from different wheat cultivars using several cysteine proteases from barley. The wide variability showed highlights the possibility to select the protease with the highest potential to alter grain composition reducing the gluten content. Consequently, new avenues could be explored combining genetic manipulation of proteolytic processes with silencing techniques to be used as biotechnological tools against gluten-related disorders.